Assessment of precision in growth inhibition assay (GIA) using human anti-PfRH5 antibodies - Kazutoyo Miura; Ababacar Diouf; Michael P. Fay; Jordan R. Barrett; Ruth O. Payne; Ally I. Olotu; Angela M. Minassian; Sarah E. Silk; Simon J. Draper; Carole A. Long (Malaria Journal, 2023)
Abstract Background For blood-stage malaria vaccine development, the in vitro growth inhibition assay (GIA) has been widely used to evaluate functionality of vaccine-induced antibodies (Ab), and Plasmodium falciparum reticulocyte-binding protein homolog 5 (RH5) is a leading blood-stage antigen. However, precision, also called “error of assay (EoA)”, in GIA readouts and the source of EoA has not been evaluated systematically. Methods In the Main GIA experiment, 4 different cultures of P. falciparum 3D7 parasites were prepared with red blood cells (RBC) collected from 4 different donors. For each culture, 7 different anti-RH5 Ab (either monoclonal or polyclonal Ab) were tested by GIA at two concentrations on three different days (168 data points). To evaluate sources of EoA in % inhibition in GIA (%GIA), a linear model fit was conducted including donor (source of RBC) and day of GIA as independent variables. In addition, 180 human anti-RH5 polyclonal Ab were tested in a Clinical GIA experiment, where each Ab was tested at multiple concentrations in at least 3 independent GIAs using different RBCs (5,093 data points). The standard deviation (sd) in %GIA and in GIA50 (Ab concentration that gave 50%GIA) readouts, and impact of repeat assays on 95% confidence interval (95%CI) of these readouts was estimated. Results The Main GIA experiment revealed that the RBC donor effect was much larger than the day effect, and an obvious donor effect was also observed in the Clinical GIA experiment. Both %GIA and log-transformed GIA50 data reasonably fit a constant sd model, and sd of %GIA and log-transformed GIA50 measurements were calculated as 7.54 and 0.206, respectively. Taking the average of three repeat assays (using three different RBCs) reduces the 95%CI width in %GIA or in GIA50 measurements by ~ half compared to a single assay. Conclusions The RBC donor effect (donor-to-donor variance on the same day) in GIA was much bigger than the day effect (day-to-day variance using the same donor’s RBC) at least for the RH5 Ab evaluated in this study; thus, future GIA studies should consider the donor effect. In addition, the 95%CI for %GIA and GIA50 shown here help when comparing GIA results from different samples/groups/studies; therefore, this study supports future malaria blood-stage vaccine development.